Tattooed human in vitro skin model for testing the biocompatibility of tattoo inks and healing progression after tattooing - Kirsten Reddersen; Deborah Maria Gregersen; Jörg Tittelbach; Cornelia Wiegand (Scientific Reports)
Abstract Tattoos are widespread in the population. Tattoo inks, which contain a variety of ingredients among them hazardous compounds such as polyaromatic hydrocarbons, heavy metals and nanoparticles and that are made for injection into the skin, are not dermatologically tested. New testing systems for evaluation of biocompatibility of tattoo inks as composite products and the tattooing process itself are needed. This paper describes an in vitro 3D human skin model that was tattooed with black and red ink. Biocompatibility including analysis of cytotoxicity, cytokine release, and gene expression patterns of proinflammatory cytokines, proliferation markers, growth factors and structural components was investigated over a period of 7 days. Tattooing of the 3D skin model resulted in a strong inflammatory reaction comparable to in vivo observations that subsided 4 days after treatment. The subsequent healing phase was detectable in the gene expression patterns. Tattooing with two different tattoo inks resulted in distinguishable inflammatory reactions. The described 3D skin model is a useful tool for evaluation of the biocompatibility of tattoo inks and the tattooing process itself and for characterizing the healing process after tattooing.